Natural Supplementation Strategy to Improve Reproductive Performance of Betta Broodstock (Betta splendens) - Ica Marsela; Helmizuryani; Muhammad Nizar (Universitas Muhammadiyah Palembang, 2025)
This study aims to evaluate the effect of supplementation of natural ingredients in pelleted feed on gonad maturity and survival of female Betta fish (Betta splendens). The research was carried out from April to June 2025 at the Aquaculture Laboratory, Faculty of Agriculture, Muhammadiyah University, Palembang. The research design used a Completely Randomized Design (CRD) with five treatments and three replications (a total of 15 containers). The basic feed used was PF 500 pellets. Treatment consisted of: P1 (100% pellets), P2 (pellets + Lactobacillus rhamnosus 100 mg%), P3 (pellets + 100 mg astaxanthin), P4 (pellets + combination of L. rhamnosus 70% + astaxanthin 30%), and P5 (pellets + combination of 70% astaxanthin + L. rhamnosus 30%). Parameters observed included an increase in body weight and length, survival, gonad maturity level (TKG), gonad maturity index (IKG), and fecundity. The results of the study showed that 100% astaxanthin (P3) supplementation provided the most optimal results in increasing body weight, survival, gonad maturity and fecundity of female B. splendens. Length growth did not show significant differences between treatments, while water quality during the study remained in the optimal range for keeping Betta fish. These findings confirm the potential of astaxanthin as an effective natural supplement in supporting the sustainable reproductive performance of ornamental fish.